ANALISIS KEBIJAKAN PENGEMBANGAN PERIKANAN PURSE SEINE DENGAN METODE ANALYTICAL HIERARCHI PROCESS (AHP) DI PERAIRAN KABUPATEN PARIGI MOUTONG - A. Masyahoro (Universitas Tadulako, 2006)
This paper describes a study finding on the determination of various policy alternatives based on biological, technological, social and economical aspects that may be suitably applied for development of purse seine fishery. This study was conducted in the District of Parigi Moutong, Central Sulawesi from January to April 2006. This study involved 5 purse seines and their owners determined using a cencus sampling technique and 20 purposedly sampled fishermen. The primnary data collected were the yield of captured fish. The policy analyses was done using an Analytical Hierarchi Process (AHP) with Expert Choice 9.0 software on a personal computer. Results showed that adding purse seines (a ranking value of 0.49) was the most important policy that may be taken in overall effort in a sustainalbe fishery development while maintaining their current number (a values of 0.32) was considered as a moderate choice and removing it was shown to be a contradictory policy